Altruism or Money? Reducing Teacher Sorting Using Behavioral Strategies in Peru - Nicolas Ajzenman; Eleonora Bertoni; Gregory Elacqua; Luana Marotta; Carolina Méndez Vargas (Institute of Labor Economics (IZA), 2021)
Inequality in access to high-quality teachers is an important driver of student socioeconomic achievement gaps. We experimentally evaluate a novel nation-wide low-cost government program aimed at reducing teacher sorting. Specifically, we tested two behavioral strategies designed to motivate teachers to apply to job vacancies in disadvantaged schools. These strategies consisted of an "Altruistic Identity" treatment arm, which primed teachers' altruistic identity by making it more salient, and an "Extrinsic Incentives" arm, which simplified the information and increased the salience of an existing government monetary-incentive scheme rewarding teachers who work in underprivileged institutions. We show that both strategies are successful in triggering teacher candidates to apply to such vacancies, as well as make them more likely to be assigned to a final in-person evaluation in a disadvantaged school. The effect among high-performing teachers is larger, especially in the "Altruistic" arm. Our results imply that low-cost behavioral strategies can enhance the supply and quality of professionals willing to teach in high-need areas.
Keywords: I24; D91; I25; 330; identity; monetary incentives; priming; altruism; prosocial behavior; teacher sorting